(untitled) (Swiss Medical Weekly, 2017)
Demographic changes worldwide challenge the healthcare system. Advanced age is associated with a number of biological alterations that, together with concomitant comorbidities, increase the risk for functional decline by inducing functional disintegration. In this concept frailty and sarcopenia play an important role. Consequently the preservation of muscle mass and function are prominent targets of medicine in old age. In order to professionally care for persons in their last years of life several other factors influencing medical decisions regarding diagnostic and treatments are important. These factors concern the life expectancy, the person`s functional status the physicians involved in care and the family system. Balancing between over- and undertreatment in very old patients can be optimised by a goal-oriented decision making approach. Very old persons with poor decision making capacity might benefit from decisions made in a team. To be able to manage the challenges associated with the last decade of life, we need physicians who have the knowledge, the appropriate attitude towards frail old patients and the skills to communicate with different groups involved in care. Ideally old age medicine should become an integrative part of a unified national medical curriculum.